Efficient synthesis of promising liquid fuels 5-ethoxymethylfurfural from carbohydrates. (15th June 2015) - Yuan, Ziliang; Zhang, Zehui; Zheng, Judun; Lin, Jintao
Highlights: A new method was developed for the synthesis of 5-ethoxymethylfurfural (EMF). EMF was obtained in high yield of 88.4% from 5-hydroxymethylfurfural. EMF yields of 67.8% and 58.4% were obtained from fructose and inulin, respectively. The catalyst could be reused without the significant loss of its catalytic activity. Abstract: In this study, we have developed an effective method for the conversion of carbohydrates into liquid biofuels 5-ethoxymethylfurfural (EMF) over a magnetic solid acid catalyst (Fe3 O4 @CSO3 H). The as-prepared magnetic Fe3 O4 @CSO3 H catalyst showed high catalytic activity toward the synthesis of EMF from carbohydrates. The etherification of 5-hydroxymethylfurfural (HMF) with ethanol over Fe3 O4 @CSO3 H catalyst produced EMF with a high yield of 88.4%. The Fe3 O4 @CSO3 H catalyst also showed high activity toward the one-pot conversion of fructose based carbohydrates into EMF. EMF was obtained in a yield of 67.8% from fructose, and that was 58.4% from inulin. The Fe3 O4 @CSO3 H catalyst could be easily collected by an external magnet and reused for several times without the significant loss of its catalytic activity.